2016
DOI: 10.1007/s10144-016-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

Association patterns and population dynamics of bottlenose dolphins in the Strait of Sicily (Central Mediterranean Sea): implication for management

Abstract: An understanding of the population dynamics and social organization of cetaceans is essential to manage the influence of anthropogenic activities. In this study, the population size, site fidelity and social interactions of bottlenose dolphins in the Strait of Sicily (Italy) were investigated to provide recommendations for their conservation. Mark‐recapture analysis was based on the encounter histories of 103 marked dolphins from 2004 to 2015. The POPAN formulation of the Jolly–Seber model in MARK software was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 57 publications
8
25
0
Order By: Relevance
“…Although definitions of regular vs. rare individuals, or residents vs. transients when actual residency can be established, vary among studies, the link between site fidelity and habitat characteristics was found in other studies. For instance, populations in open habitats off Sicily (Papale et al, 2017) and in the Madeira Archipelago (Dinis et al, 2016) comprised a low proportion of residents, while studies in the enclosed Amvrakikos Gulf, Greece (Bearzi, Agazzi, Bonizzoni, Costa, & Azzellino, 2008a; Gonzalov et al, 2016) and Sado Estuary, Portugal (Augusto, Rachinas‐Lopes, & dos Santos, 2012) found a high degree of site fidelity for the local communities. In the eastern Adriatic Sea, and using the same arbitrary criteria as in this study (observed in 1 year only), 56% of all identified individuals in the island of Vis area were rare (Holcer, 2012), whereas in Slovenian and adjacent waters 48% of individuals were rare (Genov, Kotnjek, Lesjak, Hace, & Fortuna, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although definitions of regular vs. rare individuals, or residents vs. transients when actual residency can be established, vary among studies, the link between site fidelity and habitat characteristics was found in other studies. For instance, populations in open habitats off Sicily (Papale et al, 2017) and in the Madeira Archipelago (Dinis et al, 2016) comprised a low proportion of residents, while studies in the enclosed Amvrakikos Gulf, Greece (Bearzi, Agazzi, Bonizzoni, Costa, & Azzellino, 2008a; Gonzalov et al, 2016) and Sado Estuary, Portugal (Augusto, Rachinas‐Lopes, & dos Santos, 2012) found a high degree of site fidelity for the local communities. In the eastern Adriatic Sea, and using the same arbitrary criteria as in this study (observed in 1 year only), 56% of all identified individuals in the island of Vis area were rare (Holcer, 2012), whereas in Slovenian and adjacent waters 48% of individuals were rare (Genov, Kotnjek, Lesjak, Hace, & Fortuna, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bottlenose dolphins show a high diversity in site fidelity across their distribution, ranging from year-round presence in a defined area, as in Gulf of Ambracia, Greece (Gonzalvo et al, 2016), Moray Firth, Scotland (Wilson et al, 1997), and Sarasota Bay, Florida (Wells & Scott, 1990) to seasonal (Lodi, Cantor, Daura-Jorge, & Monteiro-Neto, 2014) or occasional presence (Papale et al, 2017). The site fidelity can depend on habitat type, prey availability, social structure, and natal philopatry, and is therefore indicative of the ecology of a local population (Dinis et al, 2016;Rako-Gospi c et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…), St Johns River, Florida (0.05 ± 0.02; Ermak ), Sicily, Italy (0.06 ± 0.02; Papale et al . ), and the Sado Estuary, Portugal (0.45 ± 0.15; Augusto et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern was also detected in other Mediterranean sites. For example, in the Aeolian Archipelago (Italy) females in similar reproductive status formed strong association (Blasi & Boitani, 2014), while in the Straits of Sicily social relationships among post-parturition females were identified (Papale et al, 2016).…”
Section: Social Structure Of the Entire Populationmentioning
confidence: 99%